That's not my narwhal its tummy is too squashy - Watt, Fiona; Figg, Non; Wells, Rachel (London usborne publishing, 2014)
Meet five adorable narwhals in this exciting addition to the much-loved That's not my... series. Babies and toddlers will love touching the textured patches as they meet narwhals with smooth flippers, fuzzy spots and sparkly horns. The bright pictures and textures to stroke are designed to help develop sensory and language awareness
Scientific notions
1 13
Keywords: Science